Prevalence of Hypertension in Deep and Lobar Intracerebral Hemorrhage in a Group of Iraqi Patients - Al-Saffar, Farah I.; Al-Hamadani, Hasan A.; Mohammad, Mohammad G. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Non-traumatic Intracerebral Hemorrhage (ICH) results from rupture of blood vessels in the brain. ICH categories can also be considered as being either lobar in location or within the deep white matter. Although hypertension is a major risk factor for ICH in general[11], it is commonly considered to be associated more with patients having deep than with those having lobar haemorrhage.Objectives: We investigate the relationship between hypertension and deep versus lobar intracerebral hemorrhage (ICH).Methods: a retrospective review of records of 163 patients aged 18-89 years admitted to Al-Kadhimiya Teaching Hospital (January 2008 - October 2010) and diagnosed with ICH.Results: There was no significant relationship between hypertension in deep versus lobar intracerebral hemorrhage (p=0.814)Conclusions: Although the relation between hypertension and ICH was not found to be significant, our study suggests and recommends age-appropriate investigations for patients with ICH, as well as the need to promote patients’ education with regards to this disease and the importance of adherence to treatment of risk factors.